2011
DOI: 10.1063/1.3609284
|View full text |Cite
|
Sign up to set email alerts
|

Minimising wave drag for free surface flow past a two-dimensional stern

Abstract: Free surface flow past a two-dimensional semi-infinite curved plate is considered, with emphasis given to solving the shape of the resulting wave train that appears downstream on the surface of the fluid. This flow configuration can be interpreted as applying near the stern of a wide blunt ship. For steady flow in a fluid of finite depth, we apply the Wiener-Hopf technique to solve a linearised problem, valid for small perturbations of the uniform stream. Weakly nonlinear results obtained by a forced KdV equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For example, Binder et al [30] considered flow with a curved plate and in the phase plane this gives a curved jump between trajectories and fixed points instead of the horizontal jump that we have seen for a flat plate. A similar approach has also been used to examine the waves in subcritical flow at the stern of a ship [11,85]. In these problems, the stern consists of a curved portion of the hull that is connected to a semi-infinite horizontal plate, which is assumed to have a constant pressure, P, applied to the plate as x → ∞.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Binder et al [30] considered flow with a curved plate and in the phase plane this gives a curved jump between trajectories and fixed points instead of the horizontal jump that we have seen for a flat plate. A similar approach has also been used to examine the waves in subcritical flow at the stern of a ship [11,85]. In these problems, the stern consists of a curved portion of the hull that is connected to a semi-infinite horizontal plate, which is assumed to have a constant pressure, P, applied to the plate as x → ∞.…”
Section: Discussionmentioning
confidence: 99%
“…In these problems, the stern consists of a curved portion of the hull that is connected to a semi-infinite horizontal plate, which is assumed to have a constant pressure, P, applied to the plate as x → ∞. Under these assumptions, the equations for a step Equations (26-28) with h = P are the same as those for flow at the stern of a ship, and furthermore, Ogilat et al [85] showed that an exact solution to Equation (28) is given in terms of Jacobian elliptic functions.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] The plate considered can either be horizontal for mathematical simplicity 13 or curved for a better representation of a ship's hull. 12,33,43 For the following work, we only consider a horizontal plate in an infinitely deep fluid. For our purposes, this flow configuration provides an interesting test case as there are semi-analytical results to compare with.…”
Section: Flow Under a Semi-infinite Platementioning
confidence: 99%
“…Other early examples of similar observations are given for flows past submerged bodies and pressure distributions by Dagan [13] and Doctors & Dagan [15]. Note that these are in contrast to certain other configurations, such as flow past a semi-infinite plate [2,26,28,29,31,37], for which solutions with downstream waves do not exist for sufficiently small Froude numbers, and so there is no corresponding small Froude number nonuniformity.…”
Section: Introductionmentioning
confidence: 95%